2022
DOI: 10.3390/s22020626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GNWs/NiO-WO3/GNWs Heterostructure for NO2 Gas Sensing at Room Temperature

Abstract: Recently, as air pollution and particulate matter worsen, the importance of a platform that can monitor the air environment is emerging. Especially, among air pollutants, nitrogen dioxide (NO2) is a toxic gas that can not only generate secondary particulate matter, but can also derive numerous toxic gases. To detect such NO2 gas at low concentration, we fabricated a GNWs/NiO-WO3/GNWs heterostructure-based gas sensor using microwave plasma-enhanced chemical vapor deposition (MPECVD) and sputter, and we confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, the active layer of the CTAB functionalized SWCNTs sensor was not that stable in the range of 10-30 ppm, compared to COOH-SWCNTs (Table 1). ZnO/CuO@graphene NH 3 Jagannathan et al 30 GNWs/NiO-WO 3 /GNWs NO 2 Kwon et al 31 Pt-COFs@SnO 2 @carbon nanospheres Triethylamine Shao et al 32 (Ag)-decorated laser-induced graphene (LIG) foam (Ag/LIG) NO 2 Yang et al 33 Mousavi et al, 34 reported using MIL-101(Cr), a highly porous metal-organic framework (MOF), for fabrication of resistive gas sensor for detection of low concentration volatile organic compounds (VOCs). The authors synthesized MIL-101(Cr)/CNT nanocomposite for sensing of methanol, ethanol, formaldehyde, isopropanol, acetone, tetrahydrofuran, acetonitrile, dichloromethane, and n-hexane at room temperature.…”
Section: Carbon-based Nano Sensorsmentioning
confidence: 99%
“…However, the active layer of the CTAB functionalized SWCNTs sensor was not that stable in the range of 10-30 ppm, compared to COOH-SWCNTs (Table 1). ZnO/CuO@graphene NH 3 Jagannathan et al 30 GNWs/NiO-WO 3 /GNWs NO 2 Kwon et al 31 Pt-COFs@SnO 2 @carbon nanospheres Triethylamine Shao et al 32 (Ag)-decorated laser-induced graphene (LIG) foam (Ag/LIG) NO 2 Yang et al 33 Mousavi et al, 34 reported using MIL-101(Cr), a highly porous metal-organic framework (MOF), for fabrication of resistive gas sensor for detection of low concentration volatile organic compounds (VOCs). The authors synthesized MIL-101(Cr)/CNT nanocomposite for sensing of methanol, ethanol, formaldehyde, isopropanol, acetone, tetrahydrofuran, acetonitrile, dichloromethane, and n-hexane at room temperature.…”
Section: Carbon-based Nano Sensorsmentioning
confidence: 99%
“…The response value of the sample to 60 ppm NO 2 is as high as 33.6, which is superior than those from most of the reported Cu 2 O-based NO 2 gas sensing materials [9-12, 27, 28], as summarized in Table 1. Moreover, NO 2 gas sensing performances of the recently reported p-type metal oxides [29][30][31][32][33][34] have also been summarized in Table S1. By comparison, the gas sensing performance of Cu 2 O@Cu 1.75 S to NO 2 is comparable to those of the recently reported p-type metal oxides.…”
Section: Structure and Morphology Characterizations Of The Sensing Ma...mentioning
confidence: 99%
“…Over the past 10-15 years, many gas sensing devices based on CNWs have been developed for detection of oxygen, nitrogen dioxide, carbon monoxide, ammonia, volatile organic vapors, hydrogen, etc [12,27,[54][55][56][57]. For instance, Kwon et al reported a resistive change-based CNWs/SiO 2 /Si gas sensor for RT detection of toxic gases such as ammonia (NH 3 ) and nitrogen dioxide (NO 2 ) [27].…”
Section: Introductionmentioning
confidence: 99%